CHARACTER EDUCATION OF THE HISTORY OF ISLAMIC CIVILIZATION - Imam Tabroni; Rini Purnama Sari; Rahmat Apendi; Deden Kurnia Adam (Sekolah Tinggi Ilmu Tarbiyah Togo Ambarsari, 2022)
The history of Islamic civilization has contributed a lot to Islamic values which are very influential, especially in social science and education which if an education is not accompanied by good character, then an education is not perfect. Therefore, Islam has provided a role model in the form of Aklhalkul karimah that we can emulate and make the form of implementation of an education and educational process. We find many books with character matching as the main capital of education, even the Al-Qur’an explains a lot about the character and personality of Rasulullah SAW. Thus, with the power of the Al-Qur’an itself, it becomes a symbol that character is indeed a tool, media and model that can be used in interacting, socializing, organizing and leading the community or family. Character is a process or never ending process as long as humans live in a social environment (Thomas lickona), character is also one of the most important communication tools in the social and social world, social itself has the meaning of life that is in contact with groups or community interactions. 'Indonesian Dictionary'', Looking at the history of Islamic civilization, we can find all the characters in the Al-Qur’an from the role models of the Prophet's companions during his leadership. The history of Islamic civilization during the time of Abu Bakr Assiddiq has made a number of great achievements of the Muslims because there are also many characters that can be taken from the leadership of this khlifatul Rasullulah Saw, from the character of discipline, firmness, honesty, courage, tenacity, patience, discipline, toleranc , loving, responsible.